Yielding of male-sterile and fertile on maize hybrids at two locations in High Valley of Mexico - Tadeo-Robledo, Margarita; Espinosa-Calderón Alejandro; Turrent-Fernández Antonio; Zamudio-González Benjamín; Sierra-Macías Mauro; Gómez-Montiel Noel; Valdivia-Bernal, Roberto; Virgen-Vargas, Juan (Revista Mexicana de Ciencias Agrícolas, 2018)
In this paper five trilinear maize hybrids (H-53 AE1, AE2 H-53, H-47 AER1, Aer2 H-47, H-48 AE1) were evaluated in male-sterile and fertile in two locations of Valles Altos. The aim was to define the productive capacity of each. The research was conducted in the spring 2010 cycle, in the Experimental Field Valle de Mexico (CEVAMEX) and the Faculty of Higher Cuautitlán (FESC). The treatments in the study were: the trilinear hybrids, the male sterile and fertile versions and two locations. Statistical analysis was carried out as factorial factors considering hybrids, male sterility/fertility, locations and interactions. To yield significant differences were observed for locations as well as hybrids, but not for the male sterility/fertility factor. It was concluded that the town FESC (9 340 kg ha-1) was higher than the average of CEVAMEX (7 141 kg ha-1). The highest yield was obtained with the hybrid H-53AE1 with 9226 and the lowest was AE1 H-48 (7 617 kg ha-1). It was found that the mean of the male sterile version, considering all genotypes and both localities exhibited a yield of 8 498 kg ha-1, statistically similar to the performance of the fertile version (7 983 kg ha-1).